Producción de plántulas de Gmelina arborea roxb (MELINA) aplicando hongos formadores de micorrizas del género trichoderma como promotores del crecimiento vegetal en el cantón Quevedo provincia de los Ríos, 2022 - Gimabel Tamara, Pacho Arroyo (2022)
The main objective of the PGPMs is to evaluate the effects of inoculation, which in this case will use 3 types of strains of trichoderma fungus in seeds and seedlings of the forest species G. arborea. To do this, a completely randomized design (DCA) was established with 9 treatments and a control, each treatment with 3 repetitions and each repetition with 5 individuals.